2019
DOI: 10.2174/1573396315666190321105536
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Murmurs in Children: A Challenge For The Primary Care Physician

Abstract: : Congenital heart disease is present in almost 1% of live births and despite current progress in prenatal screening a significant percentage has delayed diagnosis or remain undiagnosed. A cardiac murmur may be the first or unique clinical sign of congenital heart disease in childhood, however, less than 1% of auscultated murmurs are of an organic cause. : Distinguishing between an innocent and a pathologic murmur can be challenging and the experience of the examiner is crucial for identifying the distinctiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 33 publications
0
22
0
3
Order By: Relevance
“…Auscultation is the primary clinical tool to identify this murmur as innocent ( 8 , 9 ). Whereas pediatric cardiologists routinely perform this task, primary care providers (PCPs) have significantly less success in distinguishing Still's murmur from the murmurs of true heart disease ( 9 , 10 ). Their identification accuracy is higher (although still poor) for pathological murmurs (41%) and other innocent murmurs (45%) ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Auscultation is the primary clinical tool to identify this murmur as innocent ( 8 , 9 ). Whereas pediatric cardiologists routinely perform this task, primary care providers (PCPs) have significantly less success in distinguishing Still's murmur from the murmurs of true heart disease ( 9 , 10 ). Their identification accuracy is higher (although still poor) for pathological murmurs (41%) and other innocent murmurs (45%) ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac murmurs in children are common 20 and usually harmless. 21 In Finland, doctors already screen children for cardiac and other major physical health problems in health checks at the ages of 4-6 weeks, 4 months, 8 months, 18 months and 4 years. The doctors reported that half of their appointments with interventions were beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Khasawneh et al also mentioned that murmurs and cyanosis are the most common clinical signs and symptoms and are the main referral indications in cyanotic CHD patients. 18,19 Cyanosis is a bluish discoloration of the skin and mucous membranes due to an increase in the concentration of reduced hemoglobin in the bloodstream. 20 In patients with cyanotic CHD, a shunt occurs from right to left and there is a mixing of oxygen-rich blood with carbon-dioxide-rich blood so that the blood flowing throughout the body has decreased oxygen saturation, resulting in manifestations of cyanosis in the patient.…”
Section: Discussionmentioning
confidence: 99%